6.22 The role of engineering thinking in social life - Salimov Baxriddin Lutfullaevich. Asqaraliev Asilxon Azizjon o‘g‘li. Murodjonov Asrorjon Ikrom o‘g‘li. (Innovative technologies in construction Scientific Journal, 2024)
Philosophical understanding of engineering thinking inevitably draws us to the center of modern worldview. Engineering thinking has a great influence on social models and accepted classifications in society. Engineering thinking based on scientific constructions also has a peculiarity of philosophical science. Key words: engineer, thinking, education, value, expert, model. Philosophical understanding of engineering thinking inevitably draws us to the center of modern worldview. Engineering thinking has a great influence on social models and accepted classifications in society. Engineering thinking based on scientific constructions also has a peculiarity of philosophical science. The complex of thinking technologies of engineering has already been formed and has been clearly and secretly existing for a long time in various spheres of science and social life with new epistemological and semiotic methods. In particular, the necessity of engineering thinking is related to the changed socio-economic conditions and socio-technological development of the economy in our country, which shows the importance of engineering thinking in the post-industrial society. One of the important principles of dialectics is the variation that is considered equally applicable to all processes in social reality. In particular, the world of professions will also change: some professions will disappear, others will be changed, and the same ones will appear for the first time. Some of these professions have existed since before, and their social importance is increasing over the years. Engineering activities also belong to the category of such professions. The uniqueness of engineering activity is that the concepts of "profession" and "specialty" are embodied in it. Also, types of mental and physical labor activities are performed on the basis of synthesis. In engineering professional studies, new professional competencies are being created and directed to various specialized fields.